Nonlinear Control of a Single Tail Tilt Servomotor Tri-Rotor Ducted VTOL-UAV - Yanpeng Hu; Jin Guo; Pei Ying; Guannan Zeng; Nanyu Chen (Aerospace, 2022)
This paper explores a novel single tail tilt servomotor tri-rotor ducted vertical takeoff and landing unmanned aerial vehicle system (VTOL-UAV), and proposes a compound control method combining disturbance observer, model predictive control (MPC) and sliding mode nonlinear dynamic inversion (NDI), and realizes the robust tracking control of the VTOL-UAV trajectory under compound disturbance. Specifically, the inner loop adopts nonlinear dynamic inverse which improved by sliding mode to realize the pseudo linearization of the system. The outer loop adopts the model predictive control based on the E-SSPC (State Space Predictive Controller based on the Error model) method, on this basis, the sliding mode disturbance observer based on fast Super-twisting algorithm is introduced into the position loop to observe and compensate the disturbance in real time, which improves the robustness of the outer loop system. Numerical simulation experiments verify the effectiveness and robustness of the control method. Finally, the flight test of the VTOL-UAV is carried out.